2006
DOI: 10.17221/5554-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The importance of increased levels of oxytocin induced by naloxone to milk removal in dairy cows

Abstract: The aim of this study was to test whether a more pronounced oxytocin release induced by naloxone during milking causes higher efficiency of milk removal. Eight pregnant multiparousHolsteincows from second to fifth lactation were used for this experiment. The experiment was carried out during three consecutive days, i.e. six milkings (three morning and three evening milkings). During first and third evening milking in cross over design (four and four animals) 250 mg of naloxone or 10 ml saline was injected 5 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…to cause its delay) or in the lack of the second emission (i.e. change in 1P milk flow type) (Negrao et al, 1999;Tančin et al, 2006). The presented data showed that changing of milking management due to OT injection and milking of only 4 ewes in one turn during the second part of the experiment has resulted in lesser occurrence of 2P milk flow and increased occurrence of 1P milk flow type.…”
Section: Milk Flow Kineticsmentioning
confidence: 72%
“…to cause its delay) or in the lack of the second emission (i.e. change in 1P milk flow type) (Negrao et al, 1999;Tančin et al, 2006). The presented data showed that changing of milking management due to OT injection and milking of only 4 ewes in one turn during the second part of the experiment has resulted in lesser occurrence of 2P milk flow and increased occurrence of 1P milk flow type.…”
Section: Milk Flow Kineticsmentioning
confidence: 72%